Isochoric thermal conductivity of solid nitrogen - Konstantinov, V.A.; Manzhelii, V.G.; Revyakin, V.P.; Sagan, V.V. (Физика низких температур, 2005)
The isochoric thermal conductivity of solid nitrogen has been investigated on four samples of
different densities in the temperature interval from 20 K to the onset of melting. In α-N₂ the
isochoric thermal conductivity exhibits a dependence weaker than Λ1/T; in β-N₂ it increases
slightly with temperature. The experimental results are discussed within a model in which the heat
is transported by low-frequency phonons or by «diffusive» modes above the mobility edge. The
growth of the thermal conductivity in β-N₂ is attributed to the decreasing «rotational» component
of the total thermal resistance, which occurs as the rotational correlations between the neighboring
molecules become weaker.